-2(5m+7)=-94

Simple and best practice solution for -2(5m+7)=-94 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5m+7)=-94 equation:


Simplifying
-2(5m + 7) = -94

Reorder the terms:
-2(7 + 5m) = -94
(7 * -2 + 5m * -2) = -94
(-14 + -10m) = -94

Solving
-14 + -10m = -94

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + -10m = -94 + 14

Combine like terms: -14 + 14 = 0
0 + -10m = -94 + 14
-10m = -94 + 14

Combine like terms: -94 + 14 = -80
-10m = -80

Divide each side by '-10'.
m = 8

Simplifying
m = 8

See similar equations:

| 11r^2-165r+5=0 | | 4(5k+3)=-128 | | 9*2x+x=95 | | 100=n-56 | | 5x+3=-4+3x+15 | | -5(2-7p)=95 | | 5x=(2x-3)(m+3) | | 6x-5(x-1)=x+3 | | 0.8(x+30)+0.2x=49 | | y=2x^2-48x+280 | | -186=3(8v+4)-6 | | -8x^2+8=o | | 10x+10=x | | -2p+8=6-(7p+5) | | (3x-24)(4x+16)+3x=14 | | 5n^2+26n-24=0 | | 2x+4x-3y= | | 2(m+3)-4=5(m+1)-6 | | (4)(-5)(-2)(-3)= | | 5p+12-8+2p=6(p+4)-2 | | 4X-30=X+39 | | 6X+10=X+75 | | -x^4+1=2x^2-3 | | 4(x+6)-10=2(2x-3) | | 2y+5=109 | | 10+10=x | | (2)(-3)(-3)(2)= | | 4X+85=X+100 | | 3m^2+m-2=0 | | 3r-6r+8+r= | | 5X-36=3X+14 | | 2x+4=3x+1+6 |

Equations solver categories